Autonomy in adolescent development : towards conceptual clarity - Petegem, Stijn Van; Soenens, Bart; Vansteenkiste, Maarten (Abingdon, Oxon ; New York, NY : Routledge, 2017)
"Autonomy is a central feature of adolescent development, playing a key role in adolescents' psychosocial adjustment. However, opinions differ about the nature and definition of autonomy and so important questions regarding the role of autonomy in adolescents' development have remained unanswered. This book helps to address these questions while bringing clarity to the literature on adolescent autonomy.Autonomy in Adolescent Development: Towards Conceptual Clarity highlights a distinction between two notions of autonomy: autonomy-as-independence and autonomy-as-volition. The chapters in this volume illustrate how this distinction sheds new light on controversial questions regarding autonomy, such as: Is more autonomy always beneficial for adolescents' psychosocial adjustment? Or are there limits to the amount of autonomy ideal for well-being and social adjustment? Is autonomy a universally critical ingredient of optimal development? Or do effects of autonomy differ by cultural context and socio-economic status? How can parents, siblings, and peers promote the development of autonomy? Bringing together scholars from varied theoretical backgrounds studying autonomy in different contexts, this book provides an overview of recent and empirical work from diverse perspectives, yielding refreshing and thought-provoking insights in the nature of adolescent autonomy. Autonomy in Adolescent Development is invaluable for advanced students and researchers in adolescent development acting both as a guide and as a source of inspiration for new research in the area."--Provided by publisher.
chapter 1 How to solve the conundrum of adolescent autonomy? -- On the importance of distinguishing between independence and volitional functioning / Bart Soenens Maarten Vansteenkiste Stijn Van Petegem Wim Beyers Richard Ryan -- chapter 2 Observing adolescent relationships -- Autonomy processes in parent, peer, and romantic partner interactions / Jessica Kansky Erik Ruzek Joseph Allen -- chapter 3 The development of autonomy during adolescence -- A social-cognitive domain theory view / Judith G. Smetana -- chapter 4 Governance transfer -- A dynamic perspective on adolescent behavioral autonomy and parent regulation / Lauree Tilton-Weaver Sheila K. Marshall -- chapter 5 Adolescent autonomy in context -- Facilitative parenting in different cultures, domains, and settings / Wendy S. Grolnick Madeline Levitt Alessandra Caruso -- chapter 6 The striving to develop an authentic inner compass as a key component of adolescents’ need for autonomy -- Parental antecedents and effects on identity, well-being, and resilience / Avi Assor -- chapter 7 The role of choice in understanding adolescent autonomy and academic functioning / Erika A. Patall Sophia Yang Hooper -- chapter 8 Parent–adolescent relationships and romantic development -- A review and argument for research on autonomy-supportive parenting / Melanie J. Zimmer-Gembeck Stijn Van Petegem Wendy Ducat Sarah Clear Shawna Mastro -- chapter 9 Psychology and culture construct “autonomy” / Çiğdem Kağıtçıbaşı.
Taylor & Francis eBook Collection
Keywords: Adolescent psychology; Autonomy in adolescence